Population Pharmacokinetics and Exposure‐Response Analyses for the Most Frequent Adverse Events Following Treatment With Lemborexant, an Orexin Receptor Antagonist, in Subjects With Insomnia Disorder. (14th July 2020) - Lalovic, Bojan; Majid, Oneeb; Aluri, Jagadeesh; Landry, Ishani; Moline, Margaret; Hussein, Ziad
Abstract: Lemborexant is a novel orexin receptor antagonist approved in the United States and Japan for the treatment of insomnia. This article describes the population pharmacokinetics (PK) of lemborexant and the relationship of its daily steady‐state exposure (Cav, ss ) to the probability of most frequent treatment‐emergent adverse events (TEAEs). The 12 230‐observation, 1892‐subject PK data set included data from 12 clinical studies with predominantly female subjects (66%) ranging in age from 18 to 88 years and from 37 to 168 kg in body weight. The 1664‐subject exposure‐response data set included data from 3 late‐stage studies. Lemborexant pharmacokinetics were described by a 3‐compartment model with combined first‐ and zero‐order absorption with lag time and linear elimination. Oral clearance decreased with increasing body mass index (exponent, −0.428), increasing alkaline phosphatase levels (exponent, −0.118), and was 26% lower in the elderly (≥65 years). Across the adverse event analysis, the frequency of subjects experiencing TEAEs during active treatment ranged from approximately 3% to 8%, in the range estimated for placebo. With and without adjustment for age, lemborexant exposure (Cav, ss ) was not a clinically meaningful linear predictor of the probability of specific TEAEs: somnolence, nasopharyngitis, flu/influenza, urinary tract infection, upper respiratory tract infection, or headache. Given the small effect sizes of covariates of the PK model and a low degree of association of lemborexant TEAEs and exposure over the range of phase 3 (therapeutic) 5‐ and 10‐mg doses, lemborexant can be safely administered without the need for dose adjustment.